Galileo, glassware, and the peacock - Reeves, Eileen A. (Quaderni d'Italianistica, 2021)
This essay examines Galileo’s peculiar comparison of small lunar craters in 1610 in his first treatise of telescopic observations, the Sidereus Nuncius, to the eyes in a peacock’s feathers and to a particular sort of glassware, and it argues that these allusions reveal more about a certain kind of sound than about the visual appearance of the moon. Galileo’s odd analogies find subsequent development in a thought experiment relating sight, sound, and sensation in his Two New Sciences of 1638.